Recognition of forcibly curved DNA by human topoisomerase I. - Zhang, Yi. (2010)
Human topoisomerase I is a group of enzyme that is responsible for the interconversions of different topological forms of DNA molecules in vivo. One of the most significant function of it is untangling the supercoiling in DNA molecules during cellular metabolic processes like replication and transcription, by introducing a transient breakage in one strand in order to make the opposing strand pass through freely and release the stress. This paper raised a new concern that DNA curvature plays a role in the binding of topoisomerase I to supercoiled DNA molecules, which suggested possible mechanisms for topoisomerase I recognition and interaction during its catalyzing reaction. DNA minicircles with relatively few base pairs were synthesized in order to mimic the supercoiling state of DNA molecules, and its binding to topoisomerase I was proven to be efficient, which suggested a future target for topoisomerase I inhibitor.